On the LPA model with $μ_a$ = 1 - Jamieson, William T.; Merino, Orlando (Sarajevo Journal of Mathematics, 2024)
In this article we establish conditions for the local stability of the positive fixed point for the structured population model of Dennis, Desharnais, Cushing, and Costantino (or LPA model) where no adults survive longer than a single time step and when there is a specific one-parameter bifurcation. Also, we study local and global behavior of orbits for which at least one component is equal to zero, and establish conditions for the existence of a curve contained in the union of the coordinate planes which is invariant for the map associated with the model.